Організація і діяльність міліції Української РСР у 1951 р. - Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178; Ярмиш, О. Н.; Yarmysh, O. N. (Наука і правоохорона. – 2019. – № 2 (44). – С. 33-44, 2019)
У статті розглянуто організацію та основні напрями діяльності міліції в Україні у 1951 р, зважаючи на те, що проблема е малодослідженою. Автори використовували історичний принцип дослідження, вивчаючи процеси, події і факти у хронологічній послідовності з урахуванням тогочасної суспільно-політичної ситуації. Новизна статті полягає в тому, що у ній вперше предметом дослідження стала історія міліції у 1951 р, набули подальшого розвитку питання про досягнення та недоліки в її роботі у цей час, висвітлено основні аспекти діяльності міліції щодо протидії злочинності.

The organizational structure and main directions of militia activity in Ukraine in 1951 are considered. The problem is poorly investigated. It shows how the structure of the militia was reorganized, the direction of its activity was considered the main, what functions were assigned to the criminal investigation. The authors argue that another subordination of the police to the Ministry of State Security was a typical manifestation of the strengthening of Stalin’s totalitarian regime, but had little impact on the overall performance of the militia. The authors draw upon the general scientific method, which requires the unity of historical and logical approach to the analyzed material. The authors strived to adhere to the historical principle by studying the processes, events and facts in chronological order, taking into account the socio-political situation of the time. The novelty of the article lies in the fact that for the first time it studies the main directions of police work in this particular historical period - 1951, further development of the questions about the main tasks of this law enforcement agency at this time, and supplements the question about the influence of structural changes in the organization of police of the Ukrainian SSR in previous years (1949-1950) on the activities of the police in the period under study. The authors note that the results of the conversion of the criminal investigation into a criminal “sysk” were insignificant. More effective was the abolition of the zonal principle of leadership of local search agencies and the introduction of linear (by type of crime). The structure of the governing bodies of the police in 1951 is highlighted, and it is indicated what functions each of the departments had. Considerable attention is paid to highlighting the main aspects of the work of the police to combat crime and the role of individual police units in this process, and certain achievements and shortcomings in this area of the work of the law enforcement agencies have been analysed. It is noted that during the period under review the general trend of decreasing crime in the state continued, and it was achieved due to the active work of the police in previous years. Shortcomings in police work were closely related to the personnel problem: there was a lack of employees with special education, and employees with higher education were very rare. Quite a significant percentage of police officers were Ukrainians. The leadership of the Ministry of State Security quite often analyzed the state of affairs in the police, pointed out the shortcomings and demanded that they be quickly addressed. In 1951, gangsterism and significant efforts to reduce manifestations of hooliganism and counteract economic crime were actually eliminated.

В статье рассмотрена организация и основные направления деятельности милиции Украины в 1951 г. Авторы использовали исторический принцип исследования, изучая процессы, события и факты в хронологической последовательности с учетом тогдашней общественно-политической ситуации. В статье впервые предметом исследования стала история милиции в 1951 г., проанализированы достижения и недостатки в ее работе в это время, освещены основные аспекты деятельности милиции по противодействию преступности.
Organization and activities of the Ukrainian SSR militia in 1951
Греченко В. А. Організація і діяльність міліції Української РСР у 1951 р. / Греченко Володимир Анатолійович, Ярмиш Олександр Назарович // Наука і правоохорона. – 2019. – № 2 (44). – С. 33-44.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; міліція; милиция; militia; Міністерство державної безпеки; карний сиск; протидія злочинності; Министерство государственной безопасности; уголовный сыск; противодействие преступности; Ministry of State Security; criminal sysk; crime prevention